Early Detection of Anthracycline Cardiotoxicity and Improvement With Heart Failure Therapy. Issue 22 (2nd June 2015) - Cardinale, Daniela; Colombo, Alessandro; Bacchiani, Giulia; Tedeschi, Ines; Meroni, Carlo A.; Veglia, Fabrizio; Civelli, Maurizio; Lamantia, Giuseppina; Colombo, Nicola; Curigliano, Giuseppe; Fiorentini, Cesare; Cipolla, Carlo M.
Abstract : Background—: Three types of anthracycline-induced cardiotoxicities are currently recognized: acute, early-onset chronic, and late-onset chronic. However, data supporting this classification are lacking. We prospectively evaluated incidence, time of occurrence, clinical correlates, and response to heart failure therapy of cardiotoxicity. Methods and Results—: We assessed left ventricular ejection fraction (LVEF), at baseline, every 3 months during chemotherapy and for the following year, every 6 months over the following 4 years, and yearly afterward in a heterogeneous cohort of 2625 patients receiving anthracycline-containing therapy. In case of cardiotoxicity (LVEF decrease >10 absolute points, and <50%), heart failure therapy was initiated. Recovery from cardiotoxicity was defined as partial (LVEF increase >5 absolute points and >50%) or full (LVEF increase to the baseline value). The median follow-up was 5.2 (quartile 1 to quartile 3, 2.6–8.0) years. The overall incidence of cardiotoxicity was 9% (n=226). The median time elapsed between the end of chemotherapy and cardiotoxicity development was 3.5 (quartile 1 to quartile 3, 3–6) months. In 98% of cases (n=221), cardiotoxicity occurred within the first year. Twenty-five (11%) patients had full recovery, and 160 (71%) patients had partial recovery. At multivariable analysis, end-chemotherapy LVEF (hazard ratio, 1.37; 95% confidence interval, 1.33–1.42 for each percent unit decrement) and cumulative doxorubicin dose (hazard ratio, 1.09; 95% confidence interval, 1.04–1.15 for each 50 mg/m 2 increment) were independent correlates of cardiotoxicity. Conclusions—: Most cardiotoxicity after anthracycline-containing therapy occurs within the first year and is associated with anthracycline dose and LVEF at the end of treatment. Early detection and prompt therapy of cardiotoxicity appear crucial for substantial recovery of cardiac function.